THE GENUS DANOCRANIA ROSENKRANTZ 1964 (CRANIIDA, BRACHIOPODA) AND ITS REPRESENTATIVES FROM THE DANIAN STAGE IN THE CRIMEA - Shapovalov A.V.; Alekseyev A.E. (My University, 1997)
Representatives of the genus Danocrania Rosenkrantz 1964 from the Danian stage in the Crimea are presented, and the distinguishing features of this genus are described. Seven morphological types of brachiopods belonging to the genus Danocrania from the Danian in the Crimea are identified. The material for the study was collected by the author in 1993 or provided by other researchers. The material was compared with specimens from collections in Western Europe.
Keywords: Danian; Cenozoic::Paleogene::Paleocene::Danian; Кайнозой::Палеоген::Палеоцен::Датский